2013
DOI: 10.1371/journal.pone.0056750
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum and Urinary Magnesium with the Pre-Diabetes, Diabetes and Diabetic Complications in the Chinese Northeast Population

Abstract: The effect of magnesium (Mg) deficiency on the prevalence of diabetes and diabetic complications has received a great attention. The present study investigated the association of Mg level in the serum or urine of the patients, lived in the Northeast areas of China, with either pre-diabetes or diabetes with and without complications. From January 2010 to October 2011, patients with type 1 diabetes (T1D, n = 25), type 2 diabetes (T2D, n = 137), impaired fasting glucose (IFG, n = 12) or impaired glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 31 publications
9
56
0
3
Order By: Relevance
“…In this study, we found that the levels of magnesium in type 1 diabetic patients at different growth stages were lower than those in the control group, but we observed no differences between genders or growth stages, which were in accordance with results from previous studies [11,12]. Wegner et al and Xu et al reported that the levels of serum magnesium in young adults with type 1 diabetes were lower than those in the control group [11,12].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that the levels of magnesium in type 1 diabetic patients at different growth stages were lower than those in the control group, but we observed no differences between genders or growth stages, which were in accordance with results from previous studies [11,12]. Wegner et al and Xu et al reported that the levels of serum magnesium in young adults with type 1 diabetes were lower than those in the control group [11,12].…”
Section: Discussionsupporting
confidence: 92%
“…Several hypotheses have been proposed. First, a possible reason for the link between lower magnesium and in-hospital mortality is that lower magnesium at admission might reflect high BP [22,23], high blood glucose [24,25], severe state of malnutrition [26], and severe renal disease [27], which are known predictors of poor outcome and mortality of stroke in previous studies [28,29,30,31,32,33]. Second, previous animal studies indicated that magnesium could improve the blood flow in the ischemic area of the brain and enhance recovery of cellular energy metabolism after ischemia [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…11 Hypomagnesaemia is also associated with progression of diabetic complications. 6,12 Uncontrolled diabetes leads to osmotic diuresis and hypomagnesaemia 13 thus there occurs a vicious cycle 14 of hypomagnesaemia, diabetes and hypomagnesaemia. Mg supplementation helps in achieving good glycaemic control and may prevent or delay complications.…”
Section: Introductionmentioning
confidence: 99%